Targeting erythropoietin protects against proteinuria in type 2 diabetic patients and in zebrafish - She, Jianqing; Chen, Junfang; Kroll, Jens (Molecular metabolism, 2018)
Objective: Adult human kidneys produce erythropoietin (EPO), which regulates red blood cell formation; however, whether EPO also functions directly on kidney development and controls diabetic kidney disease remains unknown. Here we analyzed the role of EPO in kidney development and under hyperglycemic conditions in zebrafish and in humans. Methods: Diabetic patients and respective controls were enrolled in two cohorts. Serum EPO level and urine protein change upon human EPO administration were then analyzed. Transient knockdown and permanent knockout of EPO and EPOR in renal TG(WT1B:EGFP) zebrafish were established using the morpholino technology and CRISPR/Cas9 technology. Zebrafish embryos were phenotypically analyzed using fluorescence microscopy, and functional assays were carried out with the help of TexasRed labeled 70 kDa Dextran. Apoptosis was determined using the TUNEL assay and Annexin V staining, and caspase inhibitor zVADfmk was used for rescue experiments. Results: In type 2 diabetic patients, serum EPO level decreased with the duration of diabetes, which was linked to reduced kidney function. Human recombinant EPO supplementation ameliorated proteinuria in diabetic nephropathy patients. In zebrafish, loss-of-function studies for EPO and EPOR, showed morphological and functional alterations within the pronephros, adversely affecting pronephric structure, leading to slit diaphragm dysfunction by increasing apoptosis within the pronephros. Induction of hyperglycemia in zebrafish embryos induced pronephros alterations which were further worsened upon silencing of EPO expression. Conclusions: EPO was identified as a direct renal protective factor, promoting renal embryonic development and protecting kidneys from hyperglycemia induced nephropathy.